Mental health and coping among graduate students during the COVID-19 pandemic: a gender-based analysis - Aubin, Keira C. M.; Thachet, Tara A.; Hotston, Isabella; Thompson, Ashley M. E.; Hellemans, Kim G. C. (Frontiers in Psychiatry, 2025)
IntroductionThe COVID-19 pandemic has profoundly impacted the mental health of young adults in Canada, with research showing high rates of depression and anxiety symptomatology. Graduate students, who already experience elevated mental health challenges, represent a particularly vulnerable population—yet research examining their experiences during the pandemic remains limited. This study aims to investigate mental health and well-being outcomes, negative impacts, coping strategies, and gender differences among Canadian graduate students during the COVID-19 pandemic.MethodsA cross-sectional survey was conducted among Canadian graduate students (N = 261) to assess mental health symptoms, well-being, negative impacts, coping strategies, and gender differences during the COVID-19 pandemic using a series self-report of questionnaires (e.g. BDI, BAI, DASS-S). Data were analyzed using descriptive statistics, chi-square tests and t-tests.ResultsFindings revealed significant mental health challenges among Canadian graduate students during the pandemic, with high rates of depression, anxiety, and stress reported. Female students reported worse mental health outcomes and experienced greater negative impacts compared to males. Coping strategies predominantly involved avoidant behaviors, such as watching TV and using social media, with gender differences in coping strategies.DiscussionCompared to pre-pandemic findings, graduate students in this pandemic sample reported elevated rates of mental health challenges. Women appeared to be disproportionately impacted, reflecting the heightened mental health burden they reported during this period. Avoidant coping strategies were most commonly used—aligning with the socially isolating conditions of the pandemic—with notable gender differences in types of strategies employed.ConclusionThe COVID-19 pandemic seems to have exacerbated the mental health crisis among Canadian graduate students, with higher rates of depression, anxiety, and stress reported compared to pre-pandemic findings. Female students face heightened challenges, emphasizing the need for gender-sensitive support strategies. Universities should prioritize mental health support and promote healthy coping mechanisms to address the impacts of the pandemic on graduate student well-being.